Temporal and spatial changes of Pb in soils in Cuihu wetland, Beijing, China. Issue 8 (3rd April 2022) - Cong, Ling; Yan, Guoxin; Wu, Yanan; Zhai, Jiexiu; Dai, Liyi; Zhang, Zhenming
ABSTRACT: Protecting soil from Pb contamination has been a programme for a long time in China. However, research on lead pollution in wetlands remains rare. To understand the characteristics of Pb pollution in Beijing and the sources of contamination of different soil samples in wetlands, we collected samples during all four seasons from two soil horizons and analyzed their Pb concentrations and Pb isotope ratios. The average concentrations of Pb varied from 65.44 mg/kg in spring to 106.11 mg/kg in winter. Concentrations in autumn were significantly lower than those in spring and summer and were notably different between A and B Horizons (59.42 and 71.47 mg/kg, respectively). The Pb isotopic compositions show that Pb pollution results from a mixing of geogenic and anthropogenic materials. The ratios of 206 Pb/ 207 Pb and 206 Pb/ 208 Pb evidenced that coal combustion and vehicle exhaust are the main sources of lead contamination in the two horizons. These results will help in reducing lead contamination in soil by knowing the temporal and spatial variations and sources of lead in Beijing. GRAPHICAL ABSTRACT: UF0001